Computer games: Apprehension of learning strategies - Carlos Antonio Bruno da Silva; Vânia Cordeiro de Matos; Maria Teresa Moreno Valdés; Marilene Calderaro Munguba (Universidade de Fortaleza, 2003)
Computer games and mainly videogames have proved to be an important tendency in Brazilian children's play. They are part of the playful culture, which associates modern technology to traditional play preserving the importance of the latter. Based on Vygotsky and Chadwick's ideas, this work studies the alternatives in the use of videogame by the occupational therapist, educator or parents, aiming prevention of learning difficulty by means of apprehension of learning strategies. Sixty children were investigated under dialectic, descriptive qualitative/quantitative focus. There was a semi-structured interview, direct observation and focused group applied to this intentional sample. Out of the 60 children playing in 3 videogame rental shops in Fortaleza-CE and Quixadá-CE, 30 aged 4 to 6 years old and the other 30 aged 7 and 8. Results indicate that the determination that the videogame is played in-group favors the apprehension of learning and affective strategies, processing, and meta-cognition. Therefore, videogame can be considered an excellent resource in terms of preventing learning difficulties, enabling children to their reality.